2009
DOI: 10.5194/hess-13-1503-2009
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and validation of concentrated subsurface lateral flow paths in an agricultural landscape

Abstract: Abstract. The importance of soil water flow paths to the transport of nutrients and contaminants has long been recognized. However, effective means of detecting concentrated subsurface flow paths in a large landscape are still lacking. The flow direction and accumulation algorithm based on single-direction flow algorithm (D8) in GIS hydrologic modeling is a cost-effective way to simulate potential concentrated flow paths over a large area once relevant data are collected. This study tested the D8 algorithm for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 62 publications
(64 reference statements)
2
31
0
Order By: Relevance
“…This means that the analysis of flow paths using the D-infinity method by Tarboton (1997) may affect flow path simulation results. For example, Zhu and Lin (2009) studied the relationship between a subsurface interface DEM and a land surface DEM using a hydrologic model and reported that result of flow paths in the hydrologic modelling had almost similar results with more than 90% agreement. They then interpreted the distinction between the results of the GSTO and BSTO.…”
Section: Effects Of Topography and Soil Thickness On Prediction Accuracymentioning
confidence: 77%
“…This means that the analysis of flow paths using the D-infinity method by Tarboton (1997) may affect flow path simulation results. For example, Zhu and Lin (2009) studied the relationship between a subsurface interface DEM and a land surface DEM using a hydrologic model and reported that result of flow paths in the hydrologic modelling had almost similar results with more than 90% agreement. They then interpreted the distinction between the results of the GSTO and BSTO.…”
Section: Effects Of Topography and Soil Thickness On Prediction Accuracymentioning
confidence: 77%
“…tersheds (which are not tilled) likely promote lateral hydrological flow paths (Zhu and Lin, 2009), and lateral flow can promote NO 3 − -N transport downslope . The coincident decrease in groundwater levels and NO 3 − -N concentrations from upslope to toeslope wells in the PFS suggests PFS create a NO 3 − -N sink during lateral flow through these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Subsurface lateral flow from hillslopes and its connectivity to stream flow have been studied by monitoring the dynamics of soil moisture profiles along slopes (Lin, 2006;McNamara et al, 2005;Zhu and Lin, 2009) or trench flow below hillslopes (Newman et al, 1998;Tromp-van Meerveld and McDonnell, 2006;van Verseveld et al, 2009) or both of them (Burke and Kasahara, 2011).…”
Section: Introductionmentioning
confidence: 99%